Upaya Meningkatkan Kemampuan Menulis Deskripsi Menggunakan Media Audio Visual pada Siswa Kelas III SD Negeri Tamanan 1 Kalasan - Ririh Rahayu Retnoningsih; Heri Maria Zulfiati; Teguh Heru Prayitno (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
Learning of write descriptions in elementary schools is still low rate. Students have difficulty in expressing their opinion and ideas into descriptive writing. The purpose of this study is an effort to improve the ability to write descriptions using audio visual media in the third grade students of SD Negeri Tamanan 1 Kalasan. This type of research is a Classroom Action Research (CAR) which was held at SD Negeri Tamanan 1, Kalasan District, Sleman Regency. The subjects of this research were 29 students consisting of 14 male students and 15 female students. Data collection techniques using the rubric of performance appraisal, observation, and documentation. Data analysis techniques are analysis of test results and analysis of observational data. The results showed that the application of audio-visual media can improve the learning process of writing descriptions. The increase in the ability to write descriptions can be seen from the average value of students' descriptive writing skills in the pre-action by 54.65 to 66.18 with a success percentage of 41% or as many as 12 students in the first cycle, and in the second cycle the average value of students descriptive writing skills increased by 74, 69 with a success presentation of 75.86% or as many as 22 students. This percentage has met the indicators of success in research. It is hoped that this research can be continued and developed in order to be better and useful for the world of education, especially the world of elementary school education.